IMPACT OF DOOR-TO-BALLOON TIME ON OUTCOMES OF STEMI PATIENTS UNDERGOING PRIMARY PCI: A RETROSPECTIVE COHORT STUDY - AKBER, S; KHAN, AS; KHAN, FR (Biological and Clinical Sciences Research Journal, 2024)
ST-elevation myocardial infarction (STEMI) is a critical condition resulting from the complete occlusion of a coronary artery, requiring urgent intervention to minimize myocardial damage and improve survival. Primary percutaneous coronary intervention (PCI) is the gold standard treatment, and achieving a door-to-balloon (D2B) time of ≤90 minutes is crucial for optimizing outcomes. However, D2B times remain inconsistent across healthcare systems, leading to variations in patient outcomes. Objective: This study aimed to evaluate the impact of D2B times on in-hospital mortality and major adverse cardiac events (MACE) in STEMI patients undergoing primary PCI at a tertiary care hospital. Methods: This retrospective cohort study included 300 STEMI patients who underwent primary PCI between January 1, 2023, and December 31, 2023. The cohort was divided into two groups based on D2B times: Group A (D2B ≤90 minutes, n=150) and Group B (D2B >90 minutes, n=150). Baseline characteristics, comorbidities, and procedural details were collected from electronic health records. Statistical analyses, including multivariate logistic regression and Kaplan-Meier survival analysis, were used to assess associations between D2B time and clinical outcomes, with a significance level of p<0.05. Results: The in-hospital mortality rate was significantly lower in Group A (8%) compared to Group B (20%) (p=0.002). Additionally, MACE occurred in 16.7% of patients in Group A and 26.7% in Group B (p=0.03). Multivariate regression showed that D2B >90 minutes was an independent predictor of in-hospital mortality (OR: 2.8, 95% CI: 1.4–5.7, p=0.003). Conclusion: Reducing D2B times to ≤90 minutes significantly improves survival and reduces MACE in STEMI patients undergoing primary PCI. These findings underscore the importance of streamlining systems of care to minimize delays and optimize patient outcomes in STEMI management.